206 Follow your nose to the diagnosis. Issue 12 (14th November 2019) - Li, Vivien; Vivekanandam, Vinojini; Lunn, Michael
Abstract : A 47-year-old female presented with episodic cranial neuropathies. Over four years, she had bilateral hearing impairment. Right maxillary distribution pain was attributed to sinusitis, with subsequent sinus surgery. She developed bilateral abducens palsies and left optic neuropathy, each lasting several weeks before resolution. She was diagnosed with hypopituitarism and commenced hormonal replacement after prolonged amenorrhoea. She noticed altered smell, and most recently, developed right facial weakness, which resolved with prednisolone. MRI brain demonstrated nodular dural thickening of cranial fossa floor, with symmetrical T2 white matter and basal ganglia hyperintensity. Bloods and CSF were non-diagnostic. FDG-PET showed multifocal uptake particularly involving the upper aerodigestive tract. Differentials included inflammatory or infiltrative aetiologies. Meningeal biopsy was considered, but recent corticosteroids and hydrocortisone replacement would potentially mask tissue appearances. A history of tonsillectomy and sinus surgery four years earlier coinciding with neurological symptoms led to re-review of external histology, showing 40% of IgG-positive plasma cells expressing IgG4. IgG4 disease was diagnosed and immunosuppression commenced, with clinical stability and radiological improvement. This case illustrates the chronic fluctuating presentation of IgG4 disease, and the forensic medicine required to make a diagnosis with relevant historical histology, when both presentation and tissue have been modified by steroid treatment.